Influence of Limiting Factors on Phytoplankton and Coliform Population in an Inundated, Isolated Wetland - Kumar, JI Nirmal; Oommen, Cini (Journal of Wetlands Ecology, 2009)
The relationships of phytoplankton with physical (temperature, pH), chemical (dissolved oxygen, phosphate, sulphate and nitrate) and biotic (total and fecal coliforms) parameters were analysed for the year September 2007 to August 2008 in a seasonally inundated, isolated wetland - Malwar which is situated between 22° 36'55.78" N and 72°54'58.01" E; about 7 kilometres from Anand, near Kanjari- Boriyavi railway station, Central Gujarat, India. Phytoplankton species belonged to Cyanophyceae, Chlorophyceae, Bacillariophyceae and Euglenophyceae. Cyanophyceae members accounted for 68% of the total phytoplankton population, followed by Chlorophyceae which accounted for 23% and the rest 9% were the members of Bacillariophyceae and a single species of Euglenophyceae. ANOVA indicated significant variation in phytoplankton species richness between the two study sites (P ≤ 0.001). Significant temporal variation for Cyanophyceae density (P ≤ 0.05) was also recorded. Correlation coefficients (r) among the various hydro-chemical properties and different phytoplankton groups (densities) were calculated (correlation matrix). Key words: Phytoplankton; total coliform; fecal coliform; hydro-chemical parameters DOI: 10.3126/jowe.v3i0.2225 Journal of Wetlands Ecology, (2009) Vol. 3, pp 43-55